Evaluation of cardiac status, ascites related factors and growth performance of five commercial strains of broiler chickens - Saifali Varmaghany; Hoshang Jafari; javad (Acta Scientiarum. Animal Sciences, 2020)
The aim of the current study was to evaluate cardiac status, ascites susceptibility, thyroid hormones, some hematological parameters and performance of five commercial broiler strains. Chicks were selected from strains of Cobb, Hubbard, Ross 308, Arbor Acres, and Arian (Iranian commercial broiler strain). Management and nutritional conditions were the same for all strains. Ascites related factors, and growth performance were measured. The highest and lowest, RV weight/live weight at 21 day of age were related to Arian and Ross 308 strains, respectively (p < 0.05). The TV weight, TV weight/live weight and the RV weight/live weight were significantly different between various strains at 49 and 54 days of age (p < 0.05). Strain had no effect on RV/TV. Performance, T3 and T4 hormones, hematological parameters, and mortalities were not significantly different among the strains (p > 0.05). Ascites mortalities in the Ross 308 was zero; however, it had no significant difference with other strains (p > 0.05). It was concluded that, based on performance and physiological status, even though considered broiler strains did not differ significantly because of the same genetic programs probably, but according to the prices and market conditions each can be selected for breeding.